Comparative outcome analysis of stable mildly elevated high sensitivity troponin T in patients presenting with chest pain. A single-center retrospective cohort study. (October 2020) - Mahmoud, Osama; Mahmaljy, Hadi; Youniss, Mohamed; Hernandez Campoverde, Edwin; Elias, Hadi; Stanton, Matthew; Patel, Maulin; Hashmi, Insia; Young, Katelyn; Kuppuraju, Rajesh; Jacobs, Steven; Alsaid, Amro
Highlights: The risk of events is thought to be linear with the high-sensitivity troponin level. The absolute troponin level might not be the sole determinant of risk, however. Chest pain patients with stable low-level troponin elevation pose a challenge. High-sensitivity troponin T ≤ 50 ng/l with a rise < 5 ng/l identify a low-risk cohort. Abstract: Background: The ideal high-sensitivity troponin (hsTn) cutoff for identifying those at low risk of 30 days events is debated; however, the 99th percentile overall or gender-specific upper reference limit (URL) is most commonly used. The magnitude of risk and the best management strategy for those with low-level hsTn elevation hasn't been extensively studied. Methods: We conducted a retrospective cohort analysis including 4396 chest pain patients (542 with low-level hsTn elevation) who ruled out for myocardial infarction (MI), had a stable high-sensitivity troponin T (hsTnT) levels (defined as < 5 ng/l inter-measurements increase in hsTnT levels), and were discharged from the emergency department without further ischemic testing. The aim of the study was to compare the 30-day incidence of adverse cardiac events (ACE) between patients with undetectable high-sensitivity troponin T (hsTnT) (group 1), patients with hsTnT within the 99th percentile sex-specific URL (group 2), and patients with low-level hsTnT elevation (between the 99th percentile URL and ≤ 50 ng/l) (group 3). Results: 30-day event rates were very low 0.1%, 0.6%, and 0.4% for hsTnT groups 1, 2, and 3 respectively (overall P = 0.041, for groups 2 & 3 interaction P = 0.74). 30-day all-cause mortality, as well as 1-year all-cause and cardiovascular mortalities, occurred more frequently in those with low-level hsTnT elevation as did 1-year composite ACE. Conclusion: In conclusion, 30-day adverse event rates were very low in those with stable low-level hsTnT elevation who ruled out for MI and were discharged from the emergency department without further inpatient testing.